Thread by @mtaibbi on Thread Reader App
@mtaibbi: 1.TWITTER FILES #19 The Great Covid-19 Lie Machine Stanford, the Virality Project, and the Censorship of “True Stories” 2.“The release of Dr. Anthony Fauci’s Spring 2020 emails… has been used to exacerbate ...…